The Effect of The Study Thinking Model According to The Divergent Learning Style on The Tactical Cognitive Achievement in Volleyball for Students of The College of Physical Education، Koya University. (Raparin Journal of Humanities (RJH), 2025)
The research aims to Identify: -The difference between the study thinking model according to the divergent learning style on the tactical cognitive achievement in volleyball for studentsThe difference between the probe thinking model based on the divergent learning style and the followed method in tactical cognitive achievement in volleyball. The researcher used the experimental method for its suitability to the nature of the study، and the research sample was chosen from third-stage students in the College of physical education and sport sciences at Koya University. They were divided into two groups: an experimental group that used the probing thinking model based on the divergent learning style، and a control group that used the followed method. After that، The study material was selected then the researchers presented the educational curriculum according to (the probing thinking model based on the divergent learning style) to a group of expertise in teaching methods and volleyball fields to express their opinions and notes on the program. The study tools included the tactical cognitive achievement test in volleyball and the Kolb's scale of prevailing learning styles. Next، equivalence and homogeneity were conducted as they play an important in tactical cognitive achievement in Volleyball. After that، the educational program was completed followed by conducting the post-tests and the data was analyzed by using a number of appropriate statistics، (mean، standard deviation، mode، coefficient of variation، skewness coefficient، t-test for equal independent samples and simple correlation coefficient). It was concluded that the probing thinking model based on the divergent learning style exceeded the followed method in tactical cognitive achievement in volleyball.The researchers suggested promoting teaching strategies and models based on learning styles that develop cognitive aspects in volleyball as a divergent learning style.